Comparative Analysis of the Properties of Various Clay Bricks for Optimal Construction Material Selection - Sejuwal, Sanjaya; Subedi, Rupesh; Jonchhe, Rija; Kharbuja, Sunita; Duwal, Rajan (International Journal on Engineering Technology, 2025)
This study addresses a critical research gap in Nepal’s construction sector by providing the systematic comparison of three locally used clay bricks (Traditional, Chinese Red, and Hollow) against international and national standards. Through rigorous laboratory testing of compressive strength, water absorption, and porosity (following IS 3495:1992), the research reveals distinct performance characteristics: Chinese Red Bricks emerge as superior for structural applications (16.78 MPa strength, 10.11% absorption), Traditional Bricks offer reliable general-purpose performance (16.24 MPa strength, absorption-dependent quality), while Hollow Bricks serve best in non-structural roles due to their thermal properties (23.19% porosity) despite lower strength (11.01 MPa). The findings provide evidence-based selection criteria for Nepalese builders, with regression analysis (R² = 0.349 for Traditional Bricks) offering new insights into property-performance relationships, ultimately promoting more sustainable and optimized construction practices in the region.